2021
DOI: 10.1111/jocn.15680
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality, self‐efficacy and mental health help‐seeking in lesbian, gay, bisexual and transgender adults in Taiwan: A cross‐sectional study

Abstract: Aim and objectives The study aimed to investigate the associations of suicide risk, self‐efficacy and mental health help‐seeking among the lesbian, gay, bisexual and transgender (LGBT). Background The LGBT individuals were found to have higher risk of suicide. However, mental health promotion and suicide prevention strategies were lacking in this population. Design A cross‐sectional survey with two‐group comparison. Methods The LGBT group was recruited through snowballing method, which was then age‐matched wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
2
11
1
Order By: Relevance
“…The top 10 correlates of wanting to seek help among 2SLGBTQI+ young adults identified in our study were mainly related to mental health challenges, age, sexual and gender identity related stigma and discrimination, and ACEs (Figs 2 and 3 ). Consistent with previous research, we found an association between wanting to seek help and poor or fair self-rated mental health status [ 54 , 55 ]. Previous research reported decreased rate of seeking help among those who seriously considered or attempted suicide [ 54 , 56 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The top 10 correlates of wanting to seek help among 2SLGBTQI+ young adults identified in our study were mainly related to mental health challenges, age, sexual and gender identity related stigma and discrimination, and ACEs (Figs 2 and 3 ). Consistent with previous research, we found an association between wanting to seek help and poor or fair self-rated mental health status [ 54 , 55 ]. Previous research reported decreased rate of seeking help among those who seriously considered or attempted suicide [ 54 , 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous research, we found an association between wanting to seek help and poor or fair self-rated mental health status [ 54 , 55 ]. Previous research reported decreased rate of seeking help among those who seriously considered or attempted suicide [ 54 , 56 ]. In our study, we found increased likelihood of wanting to seek help among participants who had suicidal thoughts in the past year.…”
Section: Discussionsupporting
confidence: 91%
“…People who have suicidal ideation have a considerably increased risk of suicide compared with those who do not ( Boyer et al, 2021 ). It has been identified that MSM are at a greater risk of suicidal ideation than heterosexual men ( Ramírez et al, 2020 ; Wu & Lee, 2021 ), which may be related to the prejudice and stigma connected with their sexuality ( Blosnich et al, 2020b ; Fulginiti et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a scarcity of research examining MH help-seeking behaviour among GBMSM and none during COVID-19. Generally, GBMSM-related MH help-seeking research has predominantly focused upon identity-specific barriers that exist among GBMSM when seeking help for their MH (McDermott, 2015 ; Wu & Lee, 2021 ; Zay et al, 2021 ) such as LGBTQ stigma and a dual LGBTQ MH stigma (McDermott, 2015 ; Zay et al, 2021 ). However, since the social distancing requirements of COVID-19 shifted most health services to online (websites) or telehealth delivery (Murphy, 2020 ), we now need to understand this remote MH help-seeking, which has increased 12-fold during the pandemic (Pierce, Perrin, Tyler, McKee, & Watson, 2021 ).…”
Section: Introductionmentioning
confidence: 99%